Putting the zebu to the plough - Rabezandrina, Rene (Technical Centre for Agricultural and Rural Cooperation, 1995)
In Madagascar, where 85% of the working population earn their living through agriculture and livestock farming, farmers produce mainly rice and zebu cattle. But the country is neither able to produce enough food for its 12 million inhabitants nor...